Granulosa cells of prepubertal cattle respond to gonadotropin signaling and upregulate genes that promote follicular growth and prevent cell apoptosis. Issue 12 (28th October 2018) - Michalovic, Laura; Currin, Luke; Gutierrez, Karina; Bellefleur, Anne‐Marie; Glanzner, Werner G.; Schuermann, Yasmin; de Macedo, Mariana P.; Bohrer, Rodrigo C.; Dicks, Naomi; Lopez, Rosalba; Taibi, Milena; Madogwe, Ejimedo; et al.
Abstract : Oocytes collected from prepubertal animals are known to be less developmentally competent than those from adult animals. There is evidence suggesting that acquisition of developmental competence in bovine oocytes may be linked to the expression profile of genes in the granulosa cells (GCs). Cumulus–oocyte complexes (COC) and GCs were collected from 12 Holstein heifers between 2 and 6 months of age (nine follicle‐stimulating hormone [FSH] treated and three untreated) and eight FSH‐treated cows. The COCs from prepubertal animals were matured, fertilized, and cultured in vitro to assess development to the blastocyst stage. The relative messenger RNA (mRNA) abundance of FSHR, StAR, CYP19A1, HSD3B1, CX43, FOXO1, and XIAP in GCs were quantified by real‐time quantitative polymerase chain reaction. Results from this study revealed that GCs of prepubertal animals respond to FSH treatment by increasing mRNA levels of genes promoting estradiol synthesis and follicular growth ( FSHR and CYP19A1 ), and preventing cell apoptosis ( XIAP ), and by decreasing mRNA levels of genes promoting progesterone production ( StAR and HSD3B1 ). This study also revealed that the relative mRNA abundance of FOXO1 in GCs is associated with oocyte competence to support embryo development to the blastocyst stage in prepubertal Holstein heifers. Abstract : Ovaries of prepubertal calves are capable of responding to exogenous follicle‐stimulating hormone (FSH) with follicular development. Without FSH stimulation, prepubertal animals exhibited increased messenger RNA (mRNA) levels of genes involved in promoting progesterone production and follicular atresia. FSH treatments in prepubertal animals led to increased mRNA levels of genes promoting estradiol synthesis and follicular growth.